if you multiply two summation notation

ex.

(summation (x)) *(summation(y)) do you get (sumation (xy)) ??

Printable View

- Nov 7th 2008, 07:23 AMpandakrapdo you know the properties of summation
if you multiply two summation notation

ex.

(summation (x)) *(summation(y)) do you get (sumation (xy)) ?? - Nov 7th 2008, 07:33 AMMoo
- Nov 7th 2008, 07:35 AMpandakrap
no. it = ac + cd + ad + bd

- Nov 7th 2008, 07:47 AMMoo
So try :

$\displaystyle \left(\sum_{i=1}^2 a_i \right) \times \left(\sum_{i=1}^2 b_i \right)=(a_1+a_2) \times (b_1+b_2)$

$\displaystyle \sum_{i=1}^2 a_i b_i=a_1b_1+a_2b_2$

is $\displaystyle (a_1+a_2) \times (b_1+b_2)$ equal to $\displaystyle a_1b_1+a_2b_2$ ?

And hence is your formula correct ?

You can see here : Cauchy product - Wikipedia, the free encyclopedia for the formula of the product of two summations ;)